2008
DOI: 10.1086/592206
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Race in Science and Society: Biology Textbooks, 1952–2002

Abstract: How has growing knowledge about human genetics affected how American textbooks present race? This article analyzes 80 biology textbooks published from 1952 to 2002 to reveal that U.S. biology texts have pursued the topic of race with renewed vigor in recent years. Moreover, textbooks have redefined race as genetic without furnishing empirical evidence for this framing. The textbooks' transformation sheds light on the broader relationship between race and science in the United States, where claims about racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 24 publications
2
80
0
5
Order By: Relevance
“…First, a content analysis of news articles published between 1985 and 2008 revealed that articles about race, genetics, and health in general, and more specifically articles resembling our Backdoor Vignette, which focused on a specific health-related genetic difference between blacks and whites, increased significantly over the study period. These findings cohere with those of Morning (2008), who found that messages such as those described by Duster largely account for the reemergence of the subject of race in high school biology textbooks in the 1990s. Remarkably, indirect discussions of race in the context of medical disorders (i.e., backdoor messages) appeared in 0 percent of textbooks from 1952 to 1962 but appeared in 93 percent of textbooks from 1993 to 2002.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…First, a content analysis of news articles published between 1985 and 2008 revealed that articles about race, genetics, and health in general, and more specifically articles resembling our Backdoor Vignette, which focused on a specific health-related genetic difference between blacks and whites, increased significantly over the study period. These findings cohere with those of Morning (2008), who found that messages such as those described by Duster largely account for the reemergence of the subject of race in high school biology textbooks in the 1990s. Remarkably, indirect discussions of race in the context of medical disorders (i.e., backdoor messages) appeared in 0 percent of textbooks from 1952 to 1962 but appeared in 93 percent of textbooks from 1993 to 2002.…”
Section: Discussionsupporting
confidence: 87%
“…First, these reports communicate, with the authoritative voice of science and medicine (Morning 2008), that race is a valid and useful way of categorizing humans. In addition, rather than focusing on similarities among racial groups, these reports alert us to critical, even life-threatening differences.…”
Section: Backdoor To Eugenicsmentioning
confidence: 99%
“…The problem today is no different, except that the idea of race as biological is pervasive in our culture. Research finds that the idea of race as biology is again alive and well in high school biology textbooks (Morning 2008(Morning , 2011. Mainstream media reproduce the notion of race as biology in TV shows such as Gates' Finding Your Roots and African American Lives, in which genetic ancestry testing is used to presumably identify the racial makeup of people or to identify what region of Africa one's ancestors descended from.…”
Section: Personal Reflexive Statementmentioning
confidence: 99%
“…Racial categories are neither normative nor universal. On the contrary, all forms of racial classification are social constructions (Omi and Winant 1994;Hollinger 2006;Haney-López 2006;Morning 2008).…”
Section: Introductionmentioning
confidence: 99%